Knowledge and use of the ICF in clinical practice by physiotherapists and occupational therapists of Minas Gerais - Andrei Pereira Pernambuco; Raquel de Carvalho Lana; Janaíne Cunha Polese (Fisioterapia e Pesquisa, 2018)
ABSTRACT This study aims to evaluate the profile and knowledge of physiotherapists and occupational therapists from Minas Gerais about the International Classification of Functioning, Disability and Health (ICF) application in professional practice, trying to understand the reason for the underutilization of this universal instrument in Brazil. Observational and cross-sectional study was conducted using an online questionnaire prepared by specialists. An email was sent to all physiotherapists and occupational therapists enrolled in the Regional Council of the 4th Region. Of 22,121 emails, 1,313 were answered. 53% of the sample had graduate certificate, 65% had between two to ten years of experience, and 62% reported that clinics and patients’ houses are the places where they work. 72% of the professionals knew the ICF and 84% correctly answered the meaning of the acronym. However, 71% of professionals are unaware of the fields that make up this classification. The first contact with the ICF happened during graduation to 50% of professionals, and 28% had never had contact with ICF. 74% reported not using it in clinical practice. However, 82% of the participants believed that the use of ICF is viable in clinical practice. Most professionals had graduate certificate, worked in clinics and patients’ homes and, although most of them claim to know the ICF, the largest portion of the sample reported they did not use this classification in their professional lives, even though believing the ICF use is feasible. The lack of knowledge about the ICF prevents professionals from complying with the recommendations of the World Health Organization (WHO), the Brazilian National Health Council (CNS) and COFFITO (Brazilian Federal Council of Physical Therapy and Occupational Therapy) on the adoption of this instrument in exchange of information about health and clinical practice.